PENGARUH INTERNAL AUDIT DAN SISTEM INFORMASI AKUNTANSI TERHADAP PENGENDALIAN INTERNAL PADA RUMAH SAKIT IBU DAN ANAK ANANDA MAKASSAR - HS, Sri Wahyuni HS; Rianthy, Gina Anggi Rianthy Anggi; Azis, Nur Alimin (Universitas Patria Artha, 2025)
This study was aimed to determine the influence of internal audit and accounting information system on internal control. The type of research was quantitative. The data analysis technique used multiple linear regression analysis with the help of the statistical package for social science (SPSS). Based on the results of data analysis, it can be concluded that internal audit and accounting information system had an influence on internal control at Regional Hospital for Mothers and Children Ananda Makassar.